Computational Design of a Novel VLP-Based Vaccine for Hepatitis B Virus - Mobini, Saeed; Chizari, Milad; Mafakher, Ladan; Rismani, Elmira; Rismani, Elham (Frontiers in Immunology, 2020)
Hepatitis B virus (HBV) is a global virus responsible for a universal disease burden for millions of people. Various vaccination strategies have been developed using viral vector, nucleic acid, protein, peptide, and virus-like particles (VLP) to stimulate favorable immune responses against HBV. Given the pivotal role of specific immune responses of Hepatitis B surface antigen (HBsAg) and Hepatitis B core antigen (HBcAg) in infection control, we designed a VLP-based vaccine by placing the antibody-binding fragments of HBsAg in the major immunodominant region (MIR) epitope of HBcAg to stimulate multilateral immunity. A computational approach was employed to predict and evaluate conservation, antigenicity, allergenicity, and immunogenicity of the construct. Modeling and molecular dynamics (MD) demonstrated folding stability of HBcAg as a carrier in inserting Myrcludex and 'a' determinant of HBsAg. Regions 1 to 50 and 118 to 150 of HBsAg were considered to have the highest stability to be involved in the designed vaccine. Molecular docking revealed appropriate interactions between the B-cell epitope of the designed vaccine and antibodies. Totally, the final construct was promising for inducing humoral and cellular responses against HBV.